Protein encapsulation: a new approach for improving the capability of small-molecule fluorogenic probes. Issue 4 (17th December 2019) - Han, Hai-Hao; Sedgwick, Adam C.; Shang, Ying; Li, Na; Liu, Tingting; Li, Bo-Han; Yu, Kunqian; Zang, Yi; Brewster, James T.; Odyniec, Maria L.; Weber, Maria; Bull, Steven D.; et al.
Abstract : Herein, we report a protein-based hybridization strategy that exploits the host–guest chemistry of HSA (human serum albumin) to solubilize the otherwise cell impermeable ONOO − fluorescent probe Pinkment-OAc . Abstract : Herein, we report a protein-based hybridization strategy that exploits the host-guest chemistry of HSA (human serum albumin) to solubilize the otherwise cell impermeable ONOO − fluorescent probe Pinkment-OAc . Formation of a HSA /Pinkment-OAc supramolecular hybrid was confirmed by SAXS and solution-state analyses. This HSA /Pinkment-OAc hybrid provided an enhanced fluorescence response towards ONOO − versus Pinkment-OAc alone, as determined by in vitro experiments. The HSA /Pinkment-OAc hybrid was also evaluated in RAW 264.7 macrophages and HeLa cancer cell lines, which displayed an enhanced cell permeability enabling the detection of SIN-1 and LPS generated ONOO − and the in vivo imaging of acute inflammation in LPS-treated mice. A remarkable 5.6 fold (RAW 264.7), 8.7-fold (HeLa) and 2.7-fold increased response was seen relative to Pinkment-OAc alone at the cellular level and in vivo, respectively. We anticipate that HSA/fluorescent probe hybrids will soon become ubiquitous and routinely applied to overcome solubility issues associated with hydrophobic fluorescent imaging agents designed to detect disease related biomarkers.